2020
DOI: 10.1101/2020.11.24.395251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducible abnormalities of functional gradient reliably predict clinical and cognitive symptoms in schizophrenia

Abstract: BackgroundSchizophrenia (SZ) typically manifests heterogeneous phenotypes involving positive, negative and cognitive symptoms. However, the underlying neural mechanisms of these symptoms keep unclear. Functional gradient is a fascinating measure to characterize continuous, hierarchical organization of brain.MethodsWe aimed to investigate whether reproducible disruptions of functional gradient existed in SZ compared to normal controls (NC), and these abnormalities were associated with severity of clinical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…For example, Xia et al 42 examined the replicability for differences between major depression and healthy controls in functional brain measures based on rsfMRI dataset with 1434 participants, and found that at least 400 subjects in each group were required to replicate significant brain differences between groups. In addition, an abnormal gradient map in schizophrenia identified in a discovery dataset with 400 patients and 336 controls was found to be reproducible in the replication dataset with 279 patients and 262 controls 43 . Our study warrants further research in order to determine more specific sample size requirements for good replicability of case-control differences.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Xia et al 42 examined the replicability for differences between major depression and healthy controls in functional brain measures based on rsfMRI dataset with 1434 participants, and found that at least 400 subjects in each group were required to replicate significant brain differences between groups. In addition, an abnormal gradient map in schizophrenia identified in a discovery dataset with 400 patients and 336 controls was found to be reproducible in the replication dataset with 279 patients and 262 controls 43 . Our study warrants further research in order to determine more specific sample size requirements for good replicability of case-control differences.…”
Section: Discussionmentioning
confidence: 76%